Rattus tanezumi Temminck 1844 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus tanezumi Temminck, 1844 In Siebold, Temminck, and Schlegel, Fauna Japonica, Arnz et Socii, Lugduni Batavorum, p. 51. TYPE LOCALITY: Japan, possibly from near Nagasaki on Kyushu Isl (see Jones and Johnson, 1965). DISTRIBUTION: Apparently indigenous to SE Asia, from E Afghanistan through highlands of Nepal and N India into S and C China (incl. Hainan Isl), Korea, and mainland Indochina (incl. offshore islands) south to Isthmus of Kra; also probably native to Mergui Arch., Andaman Isls, and some of the Nicobar Isls; also in SW peninsular India. Whether native or introduced to Taiwan and Japan is unknown (but see Yosida and Harada, 1985). Most likely introduced to the Malay Peninsula and islands on the Sunda Shelf (Medway and Yong, 1976) and nearby archipelagos just off of the Shelf, including the Mentawais (Musser and Califia, 1982; Musser and Newcomb, 1983). Certainly introduced to the Cocos-Keeling Isls (Musser and Califia, 1982), the Philippines (Musser, 1977«), Sulawesi (Musser and Holden, 1991), and numerous islands east through the Moluccas and Nusa Tenggara (Musser, 1970«, 1972, 1981 c) to W New Guinea (Sody, 1941), and farther east through Micronesia to islands of Eniwetok and Fiji (Johnson, 1962«, b), but not to the Samoas where R. rattus occurs (Yosida et al., 1985). SYNONYMS: alangensis, amboinensis, andamanensis, argyraceus, auroreus, barussanoides, benguetensis, bhotia, brevicaudus Chakraborty, 1975, brevicaudus Kuroda, 1952; brunneus, bullocki, burrulus, coloratus, dammermani, dentatus, diardii, exsul, flavipectus, flebilis, fortunatus, germaini, griseiventer, holchu, insulanus, kadanus, keelingensis, kelleri, khyensis, kramensis, lalolis, lanensis, longicaudus, lontaris, macmillani, makassarius, makensis, mansorius, masaretes, mesanis, mindanensis, moheius, molliculus, moluccarius, neglectus, nezumi, obiensis, ouangthomae, palelae, palembang, panjius, pannellus, pannosus, pelengensis, pipidonis, poenitentiarii, portus, povolnyi, pulliventer, rangensis, robiginosus, robonsoni, robustulus, ...